ChemInform Abstract: Visible‐Light‐Induced Chemoselective Deboronative Alkynylation under Biomolecule‐Compatible Conditions. Issue 34 (26th August 2014) - Huang, Hanchu; Zhang, Guojin; Gong, Li; Zhang, Shuaiyan; Chen, Yiyun
Abstract A ruthenium‐catalyzed, visible‐light induced deboronative alkynylation reaction is developed.